Therapeutic role of selective preoperative embolization in patients with paragangliomas of head and neck - Sekulić, Igor; Jovanovski, Aleksandar; Kostić, Dejan; Stošić, Srboljub; Bošković-Sekulić, Jelena; Stevanović, Jelena; Rančić, Nemanja (Vojnosanitetski pregled, 2021)
Background/Aim. Paragongliomas are rare hypervascular neoplasms. The aim of this study was to present the experience in the treatment of paragangliomas using preoperative embolization. Methods. This retrospective cross-sectional study included 10 patients (7 women and 3 men; median age 55 years) with paragangliomas that were embolized before surgery. Results. Three patients had tympanicum paragangliomas, two carotid bodies, three jugular and two jugulare-tympanicum paragangliomas. During the operation, only one out of 10 patients had bleeding which required blood transfusion. This patient received 1,130 mL of blood transfusion due to surgical complication. Conclusion. Adequate preoperative selective embolization of paragangliomas is essential in the preoperative preparation of these patients, because this strategy is feasible with low complication rates.